2019
DOI: 10.1038/s41598-019-42549-4
|View full text |Cite|
|
Sign up to set email alerts
|

Visualizing flow in an intact CSF network using optical coherence tomography: implications for human congenital hydrocephalus

Abstract: Cerebrospinal fluid (CSF) flow in the brain ventricles is critical for brain development. Altered CSF flow dynamics have been implicated in congenital hydrocephalus (CH) characterized by the potentially lethal expansion of cerebral ventricles if not treated. CH is the most common neurosurgical indication in children effecting 1 per 1000 infants. Current treatment modalities are limited to antiquated brain surgery techniques, mostly because of our poor understanding of the CH pathophysiology. We lack model syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 61 publications
(64 reference statements)
0
39
0
Order By: Relevance
“…Sensory regions in olfactory organs are coloured dark green, while non-sensory regions are light green. Three-dimensional renderings of brain ventricular systems of (a') a two-day old zebrafish [32], (a'') a threemonth-old zebrafish [33], (b') a stage 45 Xenopus tropicalis [34], (c') an average adult mouse [35], and (d') an adult human [36] are shown. TV = telencephalic; DV = diencephalic ventricle; TeV = tectal ventricle; RV = rhombencephalic ventricle; LV = Lateral ventricle; 3V = 3rd ventricle; MV = mesencephalic ventricle; 4V = 4th ventricle.…”
Section: Cilia In the Inner Earmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory regions in olfactory organs are coloured dark green, while non-sensory regions are light green. Three-dimensional renderings of brain ventricular systems of (a') a two-day old zebrafish [32], (a'') a threemonth-old zebrafish [33], (b') a stage 45 Xenopus tropicalis [34], (c') an average adult mouse [35], and (d') an adult human [36] are shown. TV = telencephalic; DV = diencephalic ventricle; TeV = tectal ventricle; RV = rhombencephalic ventricle; LV = Lateral ventricle; 3V = 3rd ventricle; MV = mesencephalic ventricle; 4V = 4th ventricle.…”
Section: Cilia In the Inner Earmentioning
confidence: 99%
“…Since many physiological parameters impact the bulk flow, and are difficult to measure with high spatial and temporal resolution, most studies focus on the cilia-mediated flow along the ventricular walls. The contribution of motile cilia in CSF flow is clearly demonstrated in zebrafish [32,110], clawed frog [34,133], rodents [e.g. 123,137,139,163,164], pigs [163] and humans [123].…”
Section: Regulation Of the Csf Flowmentioning
confidence: 99%
“…Recent work by Faubel et al showed a network of streams driven by MCCs along the lateral ventricle of mouse suggesting the existence of a complex polarization along the ventricular surfaces [ 32 ]. The significance of this organization remains to be a daunting puzzle yet it is known that functional cilia are crucial for early brain development [ 33 ] (mouse, rat, pig [ 32 ], zebrafish [ 21 ], Xenopus [ 34 ], human [ 35 ]). Overall, the role of cardiac and ciliary forces in CSF circulation continues to be an area of intense research although limited by the availability of model systems and technical difficulties accessing the embryonic CNS in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Xenopus tadpole brains, although architecturally simpler, share the distinct compartmentalization of the mammalian brain with two lateral ventricles, third and fourth ventricle, but have the additional advantage of being semi-transparent during development. We have previously exploited this feature to demonstrate that the developing Xenopus brain is ciliated and to demonstrate a genetic hydrocephalus model with established hydrocephaly genes [ 34 ]. Here, we use this model to test the role of cardiac and ciliary forces on Xenopus embryonic CSF circulation as well as their role in Xenopus neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, early mouse and rat embryos as the model of mammalian were imaged using OCT to assess structural and functional birth defects [15]. Cerebrospinal fluid flow in the brain ventricles of Xenopus tropicalis was measured with OCT to study the congenital hydrocephalus pathophysiology [17]. Cerebrospinal fluid flow in the brain ventricles of Xenopus tropicalis was measured with OCT to study the congenital hydrocephalus pathophysiology [17].…”
Section: Introductionmentioning
confidence: 99%